Socio-Economic Vulnerable Women and the Influence on Children Caring in Garut District - Joko Susilo Raharjo; Hadi Prabowo; Sampara Lukman (International Journal of Science and Society, 2021)
The research aimed to assess women's attitudes toward children from low and high socio-economic backgrounds. The study sample included 300 children, 143 women and 157 boys. This research used a quantitative method with a descriptive-analysis approach. Female children were given "General Information Forms" and "Scale of Family Life and Child-Raising Attitudes," The results were analyzed using the t-test approach and Analysis of Variance. After analyzing women's attitudes toward children by gender, it was discovered that there was no statistically meaningful difference (p > 0.05) at the end of the study. Women with a lower socio-economic background were found to be more protective, more resistant to women's positions, less fitting, and more stringent disciplinarians (p 0.001). It is well recognized that people with Overprotection Syndrome have a higher risk of developing breast cancer. When the relationship between women's behaviours was considered, it was discovered that there was only a clear relationship (p 0.05) between the aspects of women's strict control and other dimensions and a connection between all maternal sizes. The difference in mood is significant (p 0.001).